COUNSELING ABOUT FARDU KIFAYAH PRACTICES AT THE AL-SAHABAH MOSQUE, WORK-INTENSIVE GRYA HOUSING - Taufik Hidayat (RADJA PUBLIKA, 2025)
Counseling on the practice of fardu kifayah is an important part of efforts to improve the understanding and skills of the Muslim community in carrying out collective obligations, especially in terms of managing corpses. This activity was carried out at the Al-Sahabah Mosque, Griya Padat Karya Housing, with the aim of providing theoretical knowledge and direct practice regarding the procedures for fardu kifayah, which include bathing, shrouding, praying, and burying the corpse according to Islamic law. The methods used in this counseling include lectures, questions and answers, and direct demonstrations of practice by competent speakers in their fields. This activity was attended by local residents with enthusiasm and resulted in an increase in the understanding and skills of participants, who previously did not know much about or understand the practice of fardu kifayah as a whole. With this counseling, it is hoped that the community will be better prepared and able to carry out the obligations of fardu kifayah independently and correctly. This activity is also a means of strengthening Islamic brotherhood and increasing social awareness in community life. Overall, this counseling has had a significant positive impact on the community around the Al-Sahabah Mosque.